When losing your job feels like losing your self - RAO, Aliya Hamid (Institutional Knowledge at Singapore Management University, 2020)
I interviewed Todd, a marketing professional, in 2014 for my forthcoming book, Crunch Time: How Married Couples Confront Unemployment, which focuses on the unemployment experiences of highly educated, married professionals with children in the U.S. Like dozens of other professionals I interviewed, Todd’s employment is key to his sense of self, determining how he measures his social status and self-worth. Yet, this self-worth is constantly threatened, because professionals like Todd have become recent casualties of a pervasive labor market uncertainty that existed long before the coronavirus pandemic.